2001
DOI: 10.1046/j.1365-2818.2001.00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Confocal laser scanning microscopy as a tool to determine cyanobacteria biomass in microbial mats

Abstract: We have developed a method based on confocal laser scanning microscopy for detection and quantification of cyanobacteria from the Ebro Delta microbial mats. Cyanobacteria play a major role as primary producers in microbial mats; it is difficult, however, to apply classical methods to estimate their biomass because they establish strong interactions with detritic particles. The protocol described here allows the localization of individual cells or filaments with micrometre precision without the need to either m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 18 publications
1
27
1
Order By: Relevance
“…Conversely, in our field study, we found the highest cyanobacteria biomass when sediment temperature was low (5.3˚C on 6/28/2011; Figure 2), and the density pattern of diatoms closely followed that of cyanobacteria. This and previous studies carried out in the Bahía Blanca estuary [35], in which microbial mat populations of cyanobacteria and diatom show peak abundances in winter and lowest biomass in summer, contrasts with the pattern reported for other temperate locations [27,36].…”
Section: Discussioncontrasting
confidence: 99%
“…Conversely, in our field study, we found the highest cyanobacteria biomass when sediment temperature was low (5.3˚C on 6/28/2011; Figure 2), and the density pattern of diatoms closely followed that of cyanobacteria. This and previous studies carried out in the Bahía Blanca estuary [35], in which microbial mat populations of cyanobacteria and diatom show peak abundances in winter and lowest biomass in summer, contrasts with the pattern reported for other temperate locations [27,36].…”
Section: Discussioncontrasting
confidence: 99%
“…For that propose, we used morphologic parameters obtained from confocal images by A. Solé et al: Biomass dynamics determined by CLSM 5 means of a computer-aided drafting program (AutoCAD release version 14) (Solé et al 2001). Confocal microscopy adds many benefits to conventional light microscopy: multidimensional imaging, resolution and contrast improvement, and optical sectioning.…”
Section: Discussionmentioning
confidence: 99%
“…This plugin calculates the ratio of threshold voxels as cyanobacterial/green algae volumes to all voxels, which represent the total volume of sediment from each binary image in every single stack. The obtained biovolume percentage was multiplied by a conversion factor of 310 fg C μm -3 to convert it to biomass (Fry 1990;Bloem et al, 1995), which has also been used previously for cyanobacteria (Solé et al, 2001;2003;. Biomass results were therefore expressed in carbon units (mg C cm -3 ) of sediment.…”
Section: Clsm-ia: Carbon Estimationmentioning
confidence: 99%